EVALUASI KUALITAS KINERJA BERDASARKAN KRITERIA MALCOLM BALDRIGE (MBCFPE) DI PT BPR DP TASPEN KC PURWOKERTO - Fakhrunisa Arifatun Ni’mah; Iis Cahya Aprilia; Parisya Nasywa Hafidatur Rofiah; Yoiz Shofwa Shafrani (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study evaluates the performance quality of PT BPR DP Taspen KC Purwokerto based on the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE). Therefore, a comprehensive evaluative approach is required to assess the extent to which the principles of performance excellence have been implemented within the organization. This study employed a quantitative descriptive method supported by literature studies and in-depth interviews with the management and employees of PT BPR DP Taspen KC Purwokerto. The collected data were analyzed using the seven MBCfPE criteria, namely leadership, strategic planning, customer focus, measurement and performance analysis, human resource management, process management, and organizational performance results. This method was used to describe the company’s actual condition and objectively assess the level of implementation of each criterion. The results showed that the performance quality of PT BPR DP Taspen KC Purwokerto based on MBCfPE was categorized as very good or Benchmark Leader. Several aspects have been implemented optimally, particularly customer focus. However, there are still aspects that need improvement, especially in strategic planning and strengthening the performance measurement and analysis system. Overall, the implementation of MBCfPE has contributed positively to improving organizational effectiveness and efficiency and has become an important foundation for continuous performance improvement.